A Pengaruh Penggunaan Media Sosial Terhadap Perkembangan Bisnis Online Shop - Susanti, Santi (CV. Kalimasada Group, 2024)
This reseacrh focuses on the problems of the relationship between social media and business communication that will affect the development of online shop businesses both partially and simultaneously. This research aims to determine the effect of social media and business communication on the development of online shop business. The subject of this research is online shop users on social media. This research using quantitative descriptive research and the instrument used is a questionnaire. Data analysis techniques used quantitative descriptive data analysis